Corticomotor Excitability during Observation and Imagination of a Work of Art - Battaglia, Fortunato; Lisanby, Sarah H.; Freedberg, David (Frontiers in Human Neuroscience, 2011)
We examine the effects of the artistic representation – here exemplifed by Michelangelo’s Expulsion from Paradise – of an action on the motor system. Using single and paired- pulse transcranial magnetic stimulation (TMS) we analyze corticomotor excitability during observation of an action in the painting, during imagery of the painting, and during observation of a photograph of the same pose. We also analyze the effects of observation of two further paintings, one showing the same muscles at rest, and in the other in a more overtly emotional context. Both observation of the Expulsion and of imagery of the painting increased cortical excitability. Neither the relaxed pose of Michelangelo’s Creation nor the flexed posture in the highly emotional context of Bellini’s Dead Christ increased cortical excitability. Observation of a photograph of the same extended pose did not increase cortical excitability either. Moreover, intracortical inhibition was reduced during imagery of the painting. Our results offer clear motor correlates of the relationship between the esthetic quality of a work and the perception of implied movement within it.